Pengaruh Lingkungan kerja dan Komitmen Organisasional Terhadap Semangat kerja Pegawai pada Dinas Pertanian Kota Bima - Merry Andriani; Kartin Aprianti; Feni Aryani (JOURNAL INTELEKTUAL, 2025)
Introduction/Objective: This study aims to determine the influence of the work environment and organizational commitment on employee morale at the Bima City Agriculture Service. Background of the Problem: The Agriculture Service has a fairly large part in good service efforts, but to achieve this, high employee morale is needed. Novelty: Different from previous studies, examining the same variables but focusing on employee morale in the agency. Research Method: This study uses a Likert scale questionnaire with a sample of 58 respondents. Findings/Results: Partially and simultaneously, the variables of the work environment and organizational commitment have a significant effect on employee morale. Conclusion: A conducive work environment will make them feel comfortable, motivated, and give their best performance. In addition, organizational commitment is an internal drive that encourages someone to work with enthusiasm, diligence, and focus on the goals they want to achieve in their work